2013
DOI: 10.2116/analsci.29.35
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetophoretic Migration Velocity of Organic Microdroplets with Surfactants Using Permanent Magnets

Abstract: ). For the 1.0 M KCl solution used in our study as the medium, the values of electric conductivity and the fluid viscosity were 0.112 S cm -1 2013

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Therefore, it is not only the stability of emulsions, but also their evaluation methods, that are quite important for use both in fundamental study and in practical application. Several analytical methods for small droplets and/or emulsions have been reported: microscopy, 16 fluorescence correlation spectroscopy, 17 fluorescence lifetime imaging, 18 magnetophoretic velocimetry, 19,20 high-frequency spectroscopy, 21 and small-angle X-ray diffraction. 22 However, direct analysis of the constituents and their concentrations is quite difficult, and these factors influence the stability of emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not only the stability of emulsions, but also their evaluation methods, that are quite important for use both in fundamental study and in practical application. Several analytical methods for small droplets and/or emulsions have been reported: microscopy, 16 fluorescence correlation spectroscopy, 17 fluorescence lifetime imaging, 18 magnetophoretic velocimetry, 19,20 high-frequency spectroscopy, 21 and small-angle X-ray diffraction. 22 However, direct analysis of the constituents and their concentrations is quite difficult, and these factors influence the stability of emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in CTAB concentration resulted in an increase in the surface conductivity. 237 It will be interesting to investigate the relationship between the surface conductivity observed by electromagnetophoretic velocimetry and zeta potential of the droplet.…”
Section: Application Of Electromagnetic Forcementioning
confidence: 99%
“…Emulsions are used in diverse applications such as foods, cosmetics, and pharmaceuticals. Many studies have been carried out concerning emulsions; in recent years, novel techniques for the preparation [1][2][3][4] and measurement/evaluation [5][6][7][8][9][10][11][12] of emulsions or droplets have been reported. Chen et al reported in situ monitoring of emulsion polymerization by Raman spectroscopy using a homopolymer as an internal standard, although the absolute Raman intensity depends on many factors, such as the solution turbidity and the particle size distribution of the dispersed phase.…”
Section: Introductionmentioning
confidence: 99%